Technology, subsistence, and mobility of Middle to Late Holocene hunter-gatherers in the southern Pampas: new archaeological data from Las Toscas shallow lake (Argentina) - Massigoge, Agustina (2021)
Despite a long history of hunter-gatherer occupation in the Pampas region starting at the end of the Pleistocene, the known archaeological record is still sparse for some periods, such as the Middle Holocene. Here, we present new archaeological data from Las Toscas shallow lake, located in the inland plains of the southern Pampas, where systematic fieldwork revealed an abundant and diverse archaeological record resulting from hunter-gatherer occupation. The aims of this study were to establish the chronology of the occupations; to evaluate the use of faunal and lithic resources; and to contribute to the understanding of hunter-gatherer land use patterns. Archaeological evidence indicates that procurement, domestic, and ritual activities were conducted around the shallow lake during the Middle and Late Holocene, including hunting of terrestrial game; tool manufacture and repair; storing and use of mineral pigments; and likely human burial practices. Evidence also suggests that the use of this locality was not continuous but redundant and that this shallow lake was a persistent place for hunter-gatherers. Faunal data agrees with regional models that propose that Lama guanicoe was the main food resource during the second half of the Middle Holocene, although a taphonomic bias in favor of larger vertebrates cannot be ruled out. The lithic assemblages suggest that artifacts entered the locality mostly as part of individual toolkits and indicate a strong preference for orthoquartzite. Finally, bone remains of extinct fauna were recovered at the locality; however, a functional association between these remains and cultural material could not be demonstrated.